Ireland : Financial Sector Assessment Program-Technical Note on Oversight of Market-Based Finance; Investment Funds and Special Purpose Entities. (IMF Staff Country Reports; Country Report ;, 2022)
This technical note considers the regulation and supervision of the market-based finance (MBF) sector in Ireland. The Irish MBF sector is dominated by investment funds (IFs), including money market funds (MMFs), while special purpose entities (SPEs) continue to represent a sizeable proportion of assets. Reflecting Ireland's position more broadly as an open and internationally oriented economy, the MBF sector generally holds non-Irish assets on behalf of non-Irish investors, although domestic interlinkages exist primarily through property funds. This combination makes the sector important from a financial stability perspective both within Ireland and globally, and underlines the importance of robust regulatory oversight and a strategic approach to managing the interaction of domestic and international financial stability objectives.